Efficient Synthesis of N-Bridged Annulenes - Jianwei Liu; Shiqing Huang; Xiaoya Sun; Xue Cheng; Guangshen Wang; Kaihang Li; Baosheng Li (Journal of the American Chemical Society, 2026)
Abstract The most commonly encountered aromatic structure is the benzenoid ring, which is observed in a wide variety of pharmaceuticals and organic materials. However, studies on nonbenzenoid conjugated polyene aromatic molecules remain scarce, largely due to synthetic challenges and inherent angle strain. Herein, we report an unprecedented single-copper relay dual-catalyzed cascade sequence for the efficient construction of a unique aromatic N-bridged [10]annulene (NBA) framework (also called cycl[3,2,2]azine), in which a copper-catalyzed 10π electrocyclization is involved. To gain insight into the reaction mechanism, a series of control experiments and density functional theory calculations were conducted. The developed reaction exhibits broad functional-group tolerance and can be extended to different classes of 14π components. Significantly, the resulting NBA compounds display strong fluorescence with full-color tunability. Therefore, these innovations not only deepen our understanding of the aromaticity of nonbenzenoid systems but also highlight the potential of metal-catalyzed electrocyclization in synthetic chemistry.